Construction of identity and CSR in social networks: Adaptation of energy companies in the post-Threads stage in Spain - Lozano González, Ana A.; Rodríguez García, Fátima (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This study evaluates the adaptation of language, messages and social media strategies of Iberdrola, Repsol, Endesa and Naturgy focused on CSR after the introduction of Threads in Europe in 2023. Objectives include investigating changes in CSR communication on Threads, examining content strategies in comparison to Instagram and “X”, analyzing interaction with audiences, and assessing the impact of Threads on CSR communication. Through content analysis and analytical tools, aspects such as frequency, reach and interaction will be compared. The study seeks to identify successful tactics and provide recommendations to optimize CSR communication on social networks in the energy sector.